SISTEM INFORMASI AKUNTANSI PENGENDALIAN PERSEDIAAN PADA SEJATI BENGKEL PURWOKERTO - Muh Sofi'i; Novita Setianti; Wika Purbasari (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2020)
Inventories are current assets, and in trading companies inventory performance will greatly affect business profitability and sustainability. In this research, the design process of Inventory Control Information System at Sejati Bengkel Purwokerto , the topic and object was chosen because Sejati Bengkel is not only engaged in car service both engines and accessories, but also operates as a distributor of spare parts, where spare parts sales are carried out in addition to external parties internal sales are also carried out to the workshop unit and the workshop is followed by selling packages (bundles) of spare parts, oil and services into one package. This Inventory Control System is compiled using PHP, Javascriptt, CSS bootstrap and for the DBMS using mySQL. The focus of the system is on managing inventory, starting with data collection, Purchase Oder (PO) to suppliers, Receiving invoices, internal sales and sales to customers. A series of modules that have been compiled, in testing conducted using the blackbox method, obtained valid results, in the sense that all modules can run well and provide information as expected in the system design carried out. In the implementation, it is recommended that the Application not only be run at the local network, but it is better if it is hosted, so that management can monitor and control inventory activity and performance optimally. In further recovery, it is recommended that the system be extended to the mobile platform and utilize the API rest for the integration of data and information with the existing system.